Some Oxidative Biomarkers and Antioxidant Genes Detection in Diabetic Male Rats - O. D. Chikezie; S. C. Meludu; I. S. I. Ogbu; I. C. Maduka; T. Ude; B. N. Egejuru (Archives of Current Research International, 2020)
Background: Diabetes mellitus is a group of metabolic disorder in which there are high blood sugar levels over a prolonged period. This study assessed the effects of diabetes on levels of some oxidative biomarkers and pattern of antioxidant genes expression in the peripheral blood cell of diabetic male rats. Methods: This is an experimental study that involved 40 apparently healthy adult male albino rats (Wistar strain) which were randomly assigned to five groups (A, B, C, D and E) of eight (8) animals each. Group A (Normal Control of 72 hours post diabetes induction), Group B (Diabetic rats of 72 hours post diabetes induction), Group C (metformin treated diabetic rats), Group D (Diabetic Control untreated) and Group E (Normal Control of 3 weeks post diabetes induction). Ten milliliters of fasting blood sample was collected from all the subjects. Serum levels of malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (Gpx), vitamin C and vitamin E as well as peripheral blood antioxidant genes (CAT and CU-ZnSOD) were analyzed using standard methods. It was analyzed statistically using SPSS version 23.0. Results: The mRNA of CAT and Cu–ZnSOD genes were up-regulated at 72 hour post diabetes induction and down regulated 3 weeks after confirmation of diabetes (P<0.05). The mean values of GPx, CAT, SOD, VIT C and VIT E were significantly higher in the treated diabetic group when compared with untreated diabetic control (P<0.05) while MDA was significantly lower in treated diabetics when compared with the untreated diabetic control (P<0.05). Also, blood mean levels of GPx, CAT, VIT C and VIT E were significantly lower in the diabetic groups (treated and untreated) when compared with non diabetic control (P<0.05) while MDA was significantly higher in the diabetic groups (treated and untreated) when compared with non diabetic control (P<0.05). Additionally, there was significant negative relationship of blood glucose with GPx in the untreated group (P<0.05). Conclusion: The study suggests that hyperglycemia can cause expression of mRNA of CAT and Cu–ZnSOD genes on the peripheral blood cell in acute condition and significant alterations of oxidative stress biomarkers; however metformin treatment has showed not only hypoglycemic effect, but also anti-oxidant properties.